Serum magnesium level and QTc interval prolongation in acute myocardial infarction patients and its correlation with arrhythmias - Mohanani, Laxmi; Deopujari, Kuldeep; Meena, Rangvendra Singh; Dubey, T. N. (International Journal of Research in Medical Sciences, 2019)
Background: Arrhythmias commonly occur early in acute myocardial infarction and remain a common cause of sudden death in AMI. Magnesium has been implicated in the pathogenesis of acute myocardial infarction and its complication like arrhythmia. Magnesium improves myocardial metabolism, inhibits calcium accumulation and myocardial cell death. It improves vascular tone, peripheral vascular resistance, after load and cardiac output and reduces cardiac arrhythmias. The objective of this study to investigate the serum magnesium level and QTc interval prolongation in AMI and its correlation with arrhythmias. Methods: In this study, 200 patients of AMI were enrolled. ECG and cardiac parameters were examined. Serum magnesium level is measured and the QTc interval was calculated. Results: MI was more prevalent in the male patients (63.3%) and age group of 41-50 years. Hypertension (35.7%), smoking (34.2%), and diabetes (23.1%) were the major risk factor for MI. Mean serum magnesium level was 1.64±0.37 among those having arrhythmia that is significantly low as compared to those having no arrhythmia among which mean serum magnesium level was 2.28±0.31 (p<0.001). Mean QTc was higher (546.88 ms vs. 404.33ms) in patients documented with arrhythmia compared with those who had no arrhythmia (p<0.001). Conclusions: In acute myocardial infarction, patients with low magnesium levels and prolonged QTc interval are more prone to get arrhythmias. So magnesium treatment can be considered in patients of acute myocardial infarction with low magnesium levels.